2012
DOI: 10.1016/j.gie.2012.03.1392
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing the 22-gauge aspiration and 22-gauge biopsy needles for EUS-guided sampling of solid pancreatic mass lesions

Abstract: Background: To overcome limitations of cytology, biopsy needles have been developed to procure histologic samples during EUS. Objective: To compare 22-gauge (G) FNA and 22G biopsy needles (FNB) for EUS-guided sampling of solid pancreatic masses. Design: Randomized trial. Setting: Tertiary-care medical center. Patients: This study involved 56 patients with solid pancreatic masses. Intervention: Sampling of pancreatic masses by using 22G FNA or 22G FNB devices. Main Outcome Measurements: Compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
294
4
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(313 citation statements)
references
References 23 publications
(28 reference statements)
13
294
4
2
Order By: Relevance
“…55 To overcome the challenges presented by the TCB needle, new 19 G and 22 G fine needle biopsy (FNB) needles (EchoTip ProCore; Cook Medical, Bloomington, IN, USA) were developed, featuring a reverse bevel to better obtain core tissue. 45 Bang et al 47 revealed similar performance of the 22 G EUS-FNB to EUS-FNA in a prospective cohort study of 56 patients with SPL, including number of needle passes, diagnostic yield, technical success, or complications. EUS-FNB yield of core tissue was not significantly different than EUS-FNA (83.3% vs 100%; P = 0.26).…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 92%
See 3 more Smart Citations
“…55 To overcome the challenges presented by the TCB needle, new 19 G and 22 G fine needle biopsy (FNB) needles (EchoTip ProCore; Cook Medical, Bloomington, IN, USA) were developed, featuring a reverse bevel to better obtain core tissue. 45 Bang et al 47 revealed similar performance of the 22 G EUS-FNB to EUS-FNA in a prospective cohort study of 56 patients with SPL, including number of needle passes, diagnostic yield, technical success, or complications. EUS-FNB yield of core tissue was not significantly different than EUS-FNA (83.3% vs 100%; P = 0.26).…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 92%
“…6,11,45 It has since become standard of care to obtain EUS-FNA of SPL based on its cytological diagnostic sensitivity exceeding 80% in cases without underlying chronic pancreatitis. 3,6,11,46,47 Recently, a meta-analysis of 33 studies by Hewitt et al 48 revealed a sensitivity of 85% (95% CI = 0.84-0.86). Beyond the reliability of EUS-FNA, it also remains a safe procedure, with multiple studies demonstrating a complication rate less than 3%.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a new generation of core biopsy needles have been introduced (Echotip Procore TM , Cook Medical, Winston-Salem, NC). Multiple prospective cohort studies have suggested a significant improvement in diagnostic yield with EUS-FNB, while one RCT and some retrospective series have shown varying results [19,22,23]. To date, there is limited published data comparing EUS-FNA and EUS-FNB with regard to diagnostic yield in pancreatic and non-pancreatic Background and study aims: Techniques to optimize endoscopic ultrasound-guided tissue acquisition (EUS-TA) in a variety of lesion types have not yet been established.…”
mentioning
confidence: 99%